Half-quantum vortices: Квантованные вихри и турбулентность - Mineev, V.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Unlike to superfluid 4He the superfluid 3He-A support the existence of vortices with half-quantum of circulation as well as single quantum vortices. The singular single quanta vortices as well as nonsingular vortices with 2 quanta of circulation have been revealed in rotating 3He-A. However, the half-quantum vortices in open geometry always possess an extra energy due to spin-orbit coupling leading to formation of domain wall at distances larger than dipole length 10–3 cm from the vortex axis. Fortunately the same magnetic dipole–dipole interaction does not prevent the existence of half-quantum vortices in the polar phase of superfluid 3He recently discovered in peculiar porous media “nematically ordered” aerogel. Here we discuss this exotic possibility. The discoveries of half-quantum vortices in triplet pairing superconductor Sr2RuO4 as well in the exciton–polariton condensates are the other parts of the story about half-quantum vortices also described in the paper.